Search for the decay B0 → ϕμ+μ- - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Kopecná, Renata; et al. (Journal of high energy physics, 2022)
A search for the decay B0 → ϕμ+μ− is performed using proton-proton collisions at centre-of-mass energies of 7, 8, and 13 TeV collected by the LHCb experiment and corresponding to an integrated luminosity of 9 fb−1. No evidence for the B0 → ϕμ+μ− decay is found and an upper limit on the branching fraction, excluding the ϕ and charmonium regions in the dimuon spectrum, of 4.4 × 10−3 at a 90% credibility level, relative to that of the $$ B_s^0 $$→ ϕμ+μ− decay, is established. Using the measured $$ B_s^0 $$→ ϕμ+μ− branching fraction and assuming a phase-space model, the absolute branching fraction of the decay B0 → ϕμ+μ− in the full q2 range is determined to be less than 3.2 × 10−9 at a 90% credibility level.
The LHCb collaboration: R. Aaij, F. Archilli, S. Bachmann, A. Berninghoff, M. Borsato, R. Caspary, Rowina, G. Frau, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecna, B. Leverington, P. Li, J. Marks, D.J. Unverzagt, U. Uwer, L. Witola, A. Zhelezov [und viele weitere]
Im Titel sind die Zeichen "0", "+", "-" jeweils hochgestellt
Gesehen am 30.06.2022